Sex-specific differences in the development of acute alcohol-induced liver steatosis in mice - Wagnerberger, Sabine; Fiederlein, Lena; Stahl, Carolin; Millonig, Gunda; Mueller, Sebastian; Bischoff, Stephan C. (Alcohol and alcoholism, 2013)
Aims: Results of several animal studies suggest that similar to humans, female rodents are more susceptible to chronic alcohol-induced liver disease (ALD). The aim of the present study was to determine whether female mice are more susceptible to acute alcohol-induced steatosis than male mice and to investigate possible mechanisms involved. Methods: Male and female C57BL/6J mice received one single dose of ethanol (6 g/kg bodyweight) or isocaloric maltose-dextrin solution intragastrically. Plasma alcohol concentration, markers of hepatic steatosis, activation of the TLR-4 signaling cascade and triglyceride export as well as lipid peroxidation and of iron metabolism were measured 12 h after acute alcohol intake. Results: In male and female ethanol-treated mice, plasma alcohol concentrations were still markedly increased 12 h after the alcohol challenge, which was associated with a significant accumulation of lipids in the liver and increase of transaminases in plasma; however, lipid accumulation was ∼3-fold higher in females in comparison with male animals. Expression of MyD88 was only found to be significantly induced in livers of female alcohol-exposed mice, whereas protein levels of ApoB were found to be significantly lower only in livers of female mice exposed to ethanol. Levels of 4-HNE protein adducts and ferritin were induced in livers of male and female ethanol-treated mice. Conclusion: Taken together, these data suggest that female mice are also more susceptible to acute alcohol-induced liver steatosis and that this involves an increased activation of TLR-4-dependent signaling pathways in the liver.
Gesehen am 23.09.2021